1998
DOI: 10.1128/cdli.5.3.294-298.1998
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lytic Bacteriophage for Control of Experimental Escherichia coli Septicemia and Meningitis in Chickens and Calves

Abstract: A lytic bacteriophage, which was previously isolated from sewage and which attaches to the K1 capsular antigen, has been used to prevent septicemia and a meningitis-like infection in chickens caused by a K1+ bacteremic strain of Escherichia coli. Protection was obtained even when administration of the phage was delayed until signs of disease appeared. The phage was able to multiply in the blood. In newly borne colostrum-deprived calves given theE. coli orally, intramuscular inoculation of phage delayed appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(146 citation statements)
references
References 29 publications
6
129
0
11
Order By: Relevance
“…Injections are commonly used to deliver bacteriophages systemically, mostly in animal models. Phages have been injected intraperitoneally (IP), [111][112][113][114][115][116] intramuscularly (IM), [117][118][119][120][121][122] subcutaneously (SC) 113,123,124 or directly into the blood intravenously (IV), [125][126][127][128][129][130] including IV administration to humans. 131,132 All types of injections have been demonstrated as efficient means of phage delivery to virtually all organs and tissues.…”
Section: Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injections are commonly used to deliver bacteriophages systemically, mostly in animal models. Phages have been injected intraperitoneally (IP), [111][112][113][114][115][116] intramuscularly (IM), [117][118][119][120][121][122] subcutaneously (SC) 113,123,124 or directly into the blood intravenously (IV), [125][126][127][128][129][130] including IV administration to humans. 131,132 All types of injections have been demonstrated as efficient means of phage delivery to virtually all organs and tissues.…”
Section: Injectionsmentioning
confidence: 99%
“…Systemically administered phages have been observed in feces of calves and mice, 117,120 in intestines of mice, rabbits and chickens 80,149,150,161 and in murine stomach. 89,139 Stomach penetration from blood was studied in a model where mice were or were not prevented to swallow.…”
Section: Phages In Organsmentioning
confidence: 99%
“…The control group consisted of animals not receiving bacteriophages. The mortality rate in the study group was 0% as compared to 100% mortality in the control group (Barrow et al 1998). Biswas et al (2002) carried out a study of bacteriophage therapy in BALB/c mice infected with a vancomycin-resistant Enterococcus sp., strain.…”
Section: A Sepsis Modelmentioning
confidence: 99%
“…Recently, well-controlled animal models have demonstrated that phages can rescue animals (chickens, mice, calves, pigs, lambs, fishes, etc.) from a variety of harmful infections, like E. coli or Salmonella infections Huggins 1982, 1983;Smith et al 1987;Berchieri et al 1991;Barrow et al 1998;Park et al 2000;Sklar and Joerger 2001;Huff et al 2002;Bru Ronda et al 2003;Huff et al 2003).…”
Section: Introductionmentioning
confidence: 99%